Sustained improvement in left ventricular function after bone marrow-derived cell therapy in patients with acute ST elevation myocardial infarction (Swiss Medical Weekly, 2012)
BACKGROUND: Intracoronary injection of autologous bone marrow-derived mononucleated cells (BM-MNC) may improve LV function shortly after acute ST elevation myocardial infarction (STEMI), but little is known about the long-term durability of the treatment effect. METHODS: In a single-centre trial a total of 60 patients with acute anterior STEMI, successful reperfusion therapy and a left ventricular ejection fraction (LVEF) of